MCT4 regulates de novo pyrimidine biosynthesis in GBM in a lactate independent manner. Issue 2 (4th January 2020) - Spina, Raffaella; Voss, Dillon M; Yang, Xiaohua; Sohn, Jason W; Vinkler, Robert; Schraner, Julianna; Sloan, Anthony; Welford, Scott M; Avril, Norbert; Ames, Heather M; Woodworth, Graeme F; Bar, Eli E
Abstract: Background: Necrotic foci with surrounding hypoxic cellular pseudopalisades and microvascular hyperplasia are histological features found in glioblastoma (GBM). We have previously shown that Monocarboxylate-transporter-4 (MCT4) is highly expressed in necrotic/hypoxic regions in GBM and that increased levels of MCT4 are associated with worse clinical outcomes. Methods: A combined transcriptomics and metabolomics analysis was performed to study the effects of MCT4-depletion in hypoxic GBM neurospheres. Stable and inducible MCT4-depletion systems were used to evaluate the effects of and underlining mechanisms associated with MCT4-depletion in vitro and in vivo, alone and in combination with radiation. Results: This study establishes that conditional depletion of MCT4 profoundly impairs self-renewal and reduces the frequency and tumorigenicity of aggressive, therapy-resistant, glioblastoma-stem-cells (GSCs). Mechanistically, we observed that MCT4-depletion induces anaplerotic glutaminolysis and abrogates de novo pyrimidine biosynthesis. The latter results in a dramatic increase in DNA damage and apoptotic cell death, phenotypes that were readily rescued by pyrimidine nucleosides supplementation. Consequently, we found that MCT4-depletion promoted a significant prolongation of survival of animals bearing established orthotopic xenografts, an effect that was extended by adjuvant treatment with focused radiation. Conclusion: Our findings establish a novel role for MCT4 as a critical regulator of cellular deoxyribonucleotide levels and provide a new therapeutic direction related to MCT4 depletion in GBM.